Gold nanocrystal-mediated sliding of doublet DNA origami filaments - Urban, Maximilian J.; Zhou, Chao; Liu, Na (Nature Communications, 2018)
Kinesin, a motor protein, moves along filaments in a walk-like fashion to transport cargo to specific places in the cell. Here, the authors developed an analogous, artificial system consisting of nanoparticles moving along DNA filaments.